Targeted RNA-sequencing analysis for fusion transcripts detection in tumor diagnostics: assessment of bioinformatic tools reliability in FFPE samples - Iolanda Capone; Fabio Bozzi; Gian Paolo Dagrada; Paolo Verderio; Elena Conca; Adele Busico; Maria Adele Testi; Valentina Monti; Matteo Duca; Claudia Proto; Silvia Damian; Alberta Piccolo; et al. (Open Exploration Publishing Inc., 2022)
Aim: Diagnostic laboratories are progressively introducing next-generation sequencing (NGS) technologies in the routine workflow to meet the increasing clinical need for comprehensive molecular characterization in cancer patients for diagnosis and precision medicine, including fusion-transcripts detection. Nevertheless, the low quality of messenger RNA (mRNA) extracted from formalin-fixed paraffin-embedded (FFPE) samples may affect the transition from traditional single-gene testing approaches [like fluorescence in situ hybridization (FISH), immunohistochemistry (IHC), or polymerase chain reaction (PCR)] to NGS. The present study is aimed at assessing the overall accuracy of RNA fusion transcripts detection by NGS analysis in FFPE samples in real-world diagnostics. Methods: Herein, NGS data from 190 soft tissue tumors (STTs) and carcinoma cases, discussed in the context of the institutional Molecular Tumor Board, are reported and analyzed by FusionPlex© Solid tumor kit through the manufacturer's pipeline and by two well-known fast and accurate open-source tools [Arriba (ARR) and spliced transcripts alignment to reference (STAR)-fusion (SFU)]. Results: The combination of FusionPlex© Solid tumor with ArcherDX® Analysis suite (ADx) analysis package has been proven to be sensitive and specific in STT samples, while partial loss of sensitivity has been found in carcinoma specimens. Conclusions: Albeit ARR and SFU showed lower sensitivity, the use of additional fusion-detection tools can contribute to reinforcing or extending the output obtained by ADx, particularly in the case of low-quality input data. Overall, our results sustain the clinical use of NGS for the detection of fusion transcripts in FFPE material.